2019
DOI: 10.1016/j.ijdrr.2019.101226
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and psychological responses of the public during a major power outage: A literature review

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…While hospitals and other critical infrastructure are typically fitted with onsite backup generation for use during blackouts, multiple studies have demonstrated the substantial effect of power disruptions on people with home medical devices. Rubin and Rogers [17] highlight how hospitals in Louisiana following Hurricane Isaac in 2012 were essentially treating "electricity emergencies" rather than medical emergencies; namely people who could no longer operate electricity dependent medical or enabling devices. Libraries and shelters set up by charities acted as "electricity shelters", reducing the burden on hospitals.…”
Section: Treating Electrical Emergenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…While hospitals and other critical infrastructure are typically fitted with onsite backup generation for use during blackouts, multiple studies have demonstrated the substantial effect of power disruptions on people with home medical devices. Rubin and Rogers [17] highlight how hospitals in Louisiana following Hurricane Isaac in 2012 were essentially treating "electricity emergencies" rather than medical emergencies; namely people who could no longer operate electricity dependent medical or enabling devices. Libraries and shelters set up by charities acted as "electricity shelters", reducing the burden on hospitals.…”
Section: Treating Electrical Emergenciesmentioning
confidence: 99%
“…In developed countries this access is taken for granted. It has been well documented that this access, when removed either by planned outages [18], accident or by extreme weather or natural disasters [12,17], imposes significant stress on vulnerable individuals.…”
Section: Collaborations Towards Better Digital Health Outcomesmentioning
confidence: 99%
“…Today, consumers bear the economic loss caused by power outage risk, and the official encouragement to prevent power outage is not reliable [46]. Performance-Based Regulation and Reward-Penalty Scheme are used to maintain the balance of power supply reliability and expense, and pay compensation to consumers [47].…”
Section: Electricity Asset Securitizationmentioning
confidence: 99%
“…In disaster contexts, populations with NCDs tend to be at greater risk of excess morbidity and mortality due to the exacerbation of their conditions, worsening of contextual conditions, disruptions to their treatments or required diets, inability to operate medical devices, and di culty accessing prescription medications (10,16,45,47,(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). Victims of large-scale, catastrophic natural disasters that destroy infrastructure, health facilities, and telecommunications are at even greater risk; yet there has been little research to understand the impacts of disasters of this magnitude on individuals with NCDs (2,4,5,47,50,(63)(64)(65).…”
Section: Introductionmentioning
confidence: 99%